How Far the Promised Land? : World Affairs and the American Civil Rights Movement from the First World War to Vietnam - Rosenberg, Jonathan, 1958- (Book collections on Project MUSE., 2006)
In examining the link between international developments and the quest for racial justice, Jonathan Rosenberg argues that civil rights leaders were profoundly interested in the world beyond America and incorporated their understanding of overseas matters into their reform program in order to fortify and legitimize the message they presented to their followers, the nation, and the international community."--Jacket